Narrativas do processo formativo: uma experiência de constituição de grupo colaborativo - Marcelino, Bernardete de Lourdes Alvares (2018)
The present study performs a description and analysis of the formative experience collaboratively developed between Coordinator and teachers. It is a qualitative research conducted in public school and, in addition, unveiling the formation of collaborative group in tessitura. Focused on stories about the experience lived by those involved in the formative experience, the study describes strategies for construction of educational projects with shared teaching, highlighting the following: talk and narrative autobiographical wheel of teachers. The study indicates the limits, possibilities of building collaborative training process as well as the deployment of strategies that provide shared decencies such as the development of collaborative projects. Expected significant contributions to teaching and construction of the training process at school, with the recognition of the word of the professionals involved whose professional experience provides advances to your pedagogical practice